Glass of the Roman world - Bayley, J. (Justine); Freestone, Ian; Jackson, Caroline M. (Oxbow Books, 2015)
"These 18 papers by renowned international scholars include studies of glass from Europe and the Near East. The authors write on a variety of topics where their work is at the forefront of new approaches to the subject. They both extend and consolidate aspects of our understanding of how glass was produced, traded and used throughout the Empire and the wider world drawing on chronology, typology, patterns of distribution, and other methodologies, including the incorporation of new scientific methods. Though focusing on a single material the papers are firmly based in its archaeological context in the wider economy of the Roman world, and consider glass as part of a complex material culture controlled by the expansion and contraction of the Empire"--Provided by publisher